New record of Cheyletiella parasitivorax (Mégnin, 1878) (Trombidiformes: Cheyletidae) from Brazil with an illustrated key to species for the genus - Barros-Battesti,Darci Moraes (2020)
Abstract The cheyletid mites that parasitize mammals have been neglected for a long time in Brazil, although they can be common on pets and cause injury to their hosts. Recently, Cheyletiella parasitivorax was found parasitizing a rabbit in Brazil which represents a new host and distribution record for the mite species. An illustrated dichotomous key for the identification of the species in this genus and data from the literature are provided.